2014
DOI: 10.1016/j.rmed.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of occupational asthma: Does cessation of exposure really improve prognosis?

Abstract: Avoiding exposure to the causative agent in patients with OA does not seem to improve prognosis in this disease. Despite these findings, there is insufficient evidence to recommend a change in current management guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Several studies of workplace interventions for OA were published after the 2011 review. With a comprehensive approach of including recently published studies, [9][10][11][12] along with those studies already identified in the 2011 Cochrane review, we produced an updated systematic review of evidence on the effectiveness of workplace interventions for the treatment of OA. 13…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of workplace interventions for OA were published after the 2011 review. With a comprehensive approach of including recently published studies, [9][10][11][12] along with those studies already identified in the 2011 Cochrane review, we produced an updated systematic review of evidence on the effectiveness of workplace interventions for the treatment of OA. 13…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that when an allergic pathology of occupational origin is diagnosed, and in particular OA, patients should be removed from their work-place. However, some studies suggest that this decision should be individualized for each patient [31][32]. A recent multicenter study in patients with diagnosed OA showed that predisposing factors for progression to severe asthma are, in this order, the existence of asthma prior to occupation, expectoration, persistence of exposure to high doses, aphonia at work, and diagnostic delay [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that patients with OA generally become less responsive to the sensitizer after complete exposure removal [ 4 ]. Nevertheless, there is insufficient scientific evidence to assert that cessation of exposure improves asthma symptoms, and many patients do not become completely unresponsive to the sensitizer [ 28 ]. In our study, asthma symptoms and functional airway abnormalities had disappeared after 90 days.…”
Section: Discussionmentioning
confidence: 99%